2013
DOI: 10.1158/0008-5472.can-13-0012
|View full text |Cite
|
Sign up to set email alerts
|

Stromally Derived Lysyl Oxidase Promotes Metastasis of Transforming Growth Factor-β–Deficient Mouse Mammary Carcinomas

Abstract: The tumor stromal environment can dictate many aspects of tumor progression. A complete understanding of factors driving stromal activation and their role in tumor metastasis is critical to furthering research with the goal of therapeutic intervention. Polyoma middle T-induced mammary carcinomas lacking the type II TGF-ß receptor (PyMTmgko) are highly metastatic compared to control PyMT-induced carcinomas (PyMTfl/fl). We hypothesized that the PyMTmgko activated stroma interacts with carcinoma cells to promote … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
158
0
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 167 publications
(169 citation statements)
references
References 34 publications
7
158
0
4
Order By: Relevance
“…The deposition and linearization of collagens at this interface, driven by the activation of resident fibroblasts and subsequent secretion of LOX, are required for malignant progression in the MMTV-Neu mammary cancer model. Building on these findings, Pickup and colleagues (24) confirmed in the PyMT model of mammary carcinoma that the source of LOX and collagen secretion is activated fibroblasts in the tumor stroma, is TGFb dependent, increases ECM stiffness, and acts to enhance metastasis (by $4-fold) in this model through increasing primary tumor escape. Thus, it is without doubt that the same cells are responsible for driving tissue fibrosis and creating fibrotic milieus at both primary tumor and secondary metastatic sites that enhance tumor progression and metastasis.…”
Section: Fibrosis and Primary Tumor Progressionmentioning
confidence: 82%
“…The deposition and linearization of collagens at this interface, driven by the activation of resident fibroblasts and subsequent secretion of LOX, are required for malignant progression in the MMTV-Neu mammary cancer model. Building on these findings, Pickup and colleagues (24) confirmed in the PyMT model of mammary carcinoma that the source of LOX and collagen secretion is activated fibroblasts in the tumor stroma, is TGFb dependent, increases ECM stiffness, and acts to enhance metastasis (by $4-fold) in this model through increasing primary tumor escape. Thus, it is without doubt that the same cells are responsible for driving tissue fibrosis and creating fibrotic milieus at both primary tumor and secondary metastatic sites that enhance tumor progression and metastasis.…”
Section: Fibrosis and Primary Tumor Progressionmentioning
confidence: 82%
“…The relevance of ECM stiffness to breast tumor metastasis was further demonstrated by transgenic mouse studies in which collagen cross-linking and ECM stiffness were manipulated. These studies identified TGF-b and microRNAs that target tumor suppressors like the PI3K repressor phosphatase and tensin homolog (PTEN) as critical molecular modulators of the durotactic phenotype (Pickup et al 2013;Mouw et al 2014). Recently, a role for ECM rigidity in promoting pancreatic tumor progression and glioblastoma aggression that expand upon in vitro studies was demonstrated (Ulrich et al 2009;Laklai et al 2016;Miroshnikova et al 2016).…”
Section: Durotaxismentioning
confidence: 99%
“…LOX families are involved in a variety of pathological processes related to connective tissue [12,13], including cancer progression and metastasis [11,14]. Involvement of the LOX family is widely accepted as a poor prognostic factor for patients with cancer [15][16][17][18][19][20]. By contrast, Kaneda et al [21] reported that LOX is a tumor suppressor gene inactivated by heavy methylation of the 5 0 untranslated region and loss of heterozygosity in gastric cancers, and several studies have reported that LOX-PP has tumor suppressor activity [22][23][24].…”
Section: Introductionmentioning
confidence: 99%